Mendongeng sebagai strategi pembelajaran karakter di TBM Nusa Bentang Saung Budaya Tatarkarang Cipatujah Tasikmalaya - Encang Saepudin; Ninis Agustini Damayani; Tine Silvana Rachmawati (Jurnal Kajian Informasi dan Perpustakaan, 2019)
Character education implementation must be integrated with various life activities. Storytelling activities can be a medium for character education, both at school and outside school. This is in line with the benefits of storytelling, namely to sharpen the imagination and thought, instill values and ethics, and improve vocabulary.  This study aimed to find out the steps of storytelling as a character learning strategy. The research method used was a qualitative case study approach. The collecting data process was through interviews, discussions, observations, and literature studies. Validity and reliability tests were through the process of data triangulation and source triangulation. Consideration of choosing this method was the research data nature, which could maintain the object integrity. This means that data relating to research was comprehended as an integrated whole. Descriptive data analysis was through the stages of data reduction, data presentation, and concluding. Data sources in the study amounted to 7 people, consisting of community and religious leaders (3 people), manager of the ‘Saung Budaya Tatarkarang’ community reading park (2 people), and the education office (2 people). The results showed that storytelling activities at ‘Saung Budaya Tatarkarang’ were able to build children's character at the stages of socialization and internalization. This occurred due to the implementation of storytelling activities through the stages of setting goals and theme of the story, the form of storytelling, materials and tools, the design steps of storytelling activities, and the design of storytelling activities assessment. These five steps are carried out in stages in each event.